Fructo-oligosaccharides alleviate inflammation-associated apoptosis of GLP-1 secreting L cells via inhibition of iNOS and cleaved caspase-3 expression - Preedajit Wongkrasant; Pawin Pongkorpsakol; Sasirin Chitwattananont; Wilasinee Satianrapapong; Nuttha Tuangkijkul; Chatchai Muanprasat (Elsevier, 2020)
Glucagon-like peptide 1 (GLP-1) released from enteroendocrine (L) cells regulates insulin secretion. Intestinal inflammation and impaired GLP-1 release have been found in type 2 diabetes mellitus (T2DM) patients. Fructo-oligosaccharides (FOS), a known prebiotic, improve GLP-1 release and glucose homeostasis in T2DM models. This study aimed to investigate the effect of tumor necrosis factor-α (TNF-α), a proinflammatory cytokine associated with intestinal inflammation in T2DM, on L cell apoptosis and the effect of FOS on inflammation-associated impairment of GLP-1 secretion. Herein, using cell death assays, immunofluorescence staining, real time PCR and Western blot analyses, we found that TNF-α induced L cell apoptosis via nuclear factor kappa B (NF-κB)- inducible nitric oxide synthase (iNOS)-cleaved caspase-3-dependent pathways. Interestingly, FOS did not suppress TNF-α-induced NF-κB nuclear translocation, but inhibited expression of iNOS and cleaved caspase-3. In addition, FOS alleviated apoptosis and rescued impaired GLP-1 release in TNF-α-treated L cells. Altogether, our data indicate that TNF-α induces L cell apoptosis via an NF-κB-iNOS-caspase-3-dependent pathway. FOS may be useful in suppressing inflammation-associated L cell apoptosis and maintaining GLP-1 level in T2DM patients.